Black Women as Learners: Adult Education and Family Literacy Program Participation among Primary Caregiving Grandmothers - Mattyna L. Stephens; Mary Alfred (Adult Education Research Conference, 2013)
The purpose of this study was to examine how Black grandmothers who are the primary caregivers promote literacy for themselves and for the grandchild or grandchildren in their care. The findings were situated into a three category model (author developed). Implications for research and practice are also provided.